Implementasi Pendekatan Saintifik Pada Materi Menulis Teks Prosedur Siswa Kelas VII C1 Di SMP N 1 Kota Jambi - Rustam Rustam (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2017)
ABSTRACT The purpose of this study is to determine the implementation of the scientific approach in planning, implementation, and evaluation of learning to write the text of student procedures in class VII CI SMP Negeri 1 Kota Jambi. This research method using qualitative descriptive method. Data were collected by using documentation method, observation, and interview. The data of this research is the lesson planning in the form of RPP, the process of writing text writing procedure in class VII CI SMP Negeri 1 Kota Jambi, transcript of interview with teacher of teaching field and documentation of learning process happened. Data analysis used is descriptive data analysis about result of assessment of planning, implementation, and evaluation of learning. Keywords: Scientific Approach, Procedure Text, Grade VII Student